(untitled) (Ius Novum, 2024)
On 1 January 2024, a new support scheme for persons with disabilities and their carers entered into force. New solutions in this regard were included in the Act of 7 July 2023 on the Support Benefit, which introduced a new benefit directly for persons with disabilities and significantly modified the catalogue of benefits available to their carers. The provisions of this Act also altered the nature of the care benefit, which, until that time, had provided compensation to carers of persons with disabilities for not being able to undertake gainful activity. At the same time the legislator, subject to certain conditions, allowed for the possibility of establishing the right to the care benefit under the terms in force until 31 December 2023. This study analyses the normative regulations applicable to acquiring the right to the care benefit after 1 January 2024, based on the regulations in force until 31 December 2023.